An Improved Modified Ghost Fluid Method for Compressible Multi-Medium Fluid Flows (Communications in Computational Physics, 2024)
Pressure dislocation might be observed when the modified ghost fluidmethod (MGFM) is applied to simulate radially symmetric multi-medium fluid flowsfor a long time. We disclose the insightful reason that the MGFM cannot satisfy balanced boundary conditions when applied to simulate the radially symmetric compressible multi-medium flows, resulting in a first-order temporal error in the interface region. To impose these balanced boundary conditions, we develop an improvedMGFM in this work. The reconstruction for the initial value of the multi-mediumRiemann problem at the interface is specially designed in combination with thesebalanced boundary conditions. In addition, the predicted instantaneous interfacestates and balanced boundary conditions are then utilized to define the ghost fluidstates. Theoretical analysis shows that the improved MGFM can satisfy these balancedboundary conditions and effectively eliminate the first-order temporal error at the interface. Its extension to two dimensions is also presented. Numerical results show thatthe proposed improved MGFM can restraint pressure dislocation and overheating atthe material interface very well and effectively improve mass conservation.
Keywords: Multi-medium compressible flows; radially symmetric flows; modified ghost fluid method; balanced boundary conditions.